A MOBILE APPLICATION DESIGN FOR RETAIL FUEL ORDERING - Bumrungskulpong, Sunat; Suesaowaluk, Poonphon (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Propose: The design of mobile application to enhance fuel ordering process is a crucial step in optimizing user expectation and satisfaction in a relationship with user interface and user experience. This research aims to identify practices in mobile application design, explore design solutions, evaluate their impact on user experience and propose a design solution for a mobile application design to be used in retail fuel ordering process in Thailand. Research design, data and methodology: A designed-based approach with multi-phase process is adapted to propose a design solution in collaboration with color theory, user interface and user experience. By leveraging analysis of practical problems in fuel ordering pain points, system solution will be developed to enhance overall user experience. Then, the proposed solution will be tested and evaluated through a collaboration of a group of diverse users. Finally, the outcome of this designed-based research is reflected and documented for further reference. Results: Mobile application design prototype that can fulfill user requirements, improve user efficiency, and gain user acceptance. Conclusions: The mobile application with user-centric employment of color theory, user interface and user experience has a constructive impact on users through enhancing human interaction and simplifying tasks.